Late quaternary speleogenesis and landscape evolution in the northern Apennine evaporite areas. Issue 10 (29th January 2017) - Columbu, Andrea; Chiarini, Veronica; De Waele, Jo; Drysdale, Russell; Woodhead, Jon; Hellstrom, John; Forti, Paolo
Abstract: Gypsum beds host the majority of the caves in the north‐eastern flank of the Apennines, in the Emilia Romagna region (Italy). More than six hundred of these caves have been surveyed, including the longest known epigenic gypsum cave systems in the world (Spipola‐Acquafredda, 11 km). Although this area has been intensively studied from a geological point of view, the age of the caves has never been investigated in detail. The rapid dissolution of gypsum and uplift history of the area have led to the long‐held view that speleogenesis commenced only during the last 130 000 years. Epigenic caves only form when the surface drainage system efficiently conveys water into the underground. In the study area, this was achieved after the dismantling of most of the impervious sediments covering the gypsum and the development of protovalleys and sinkholes. The time necessary for these processes can by constrained by understanding when caves were first formed. The minimum age of karst voids can be indirectly estimated by dating the infilling sediments. U–Th dating of carbonate speleothems growing in gypsum caves has been applied to 20 samples from 14 different caves from the Spipola‐Acquafredda, Monte Tondo‐Re Tiberio, Stella‐Rio Basino, Monte Mauro, and Castelnuovo systems. The results show that: (i) caves have been forming since at least 600 kyr ago; (ii) the peak of speleogenesis was reached during relatively cold climate stages, when rivers formed terraces at the surface and aggradation caused paragenesis in the stable cave levels; (iii) 200 000 years were necessary for the dismantling of most of the sediments covering the karstifiable gypsum and the development of a surface mature drainage network. Besides providing a significant contribution to the understanding of evaporite karst evolution in the Apennines, this study refines our knowledge on the timescale of geomorphological processes in a region affected by rapid uplifting. Copyright © 2016 John Wiley & Sons, Ltd.